The effect of Different Levels of effect of supplementing nano zinc oxide (nZnO) on the product traits Local goat Kids - Khashan, Ali; Maithem K, Ali AL-Galiby, Maithem K, Ali AL-Galiby (University of Thi-Qar Journal of agricultural research, 2025)
This experiment was conducted at the Animal Field of the College of Agriculture and Marshes, University of Thi-Qar, from September 15, 2024, to January 22, 2025, to investigate the effect of supplementing nano zinc oxide (nZnO) at three different levels (0, 20, and 30 mg/head/day) on the productive performance of local goat kids. A total of 12 local male kids, purchased from local markets in Thi-Qar Province, were randomly allocated to three experimental groups (n = 4 per group). All groups received the same concentrate diet at 3% of dry matter relative to live body weight, consisting of: barley (45%), wheat bran (25%), ground yellow corn (15%), soybean meal (12%), and a vitamin-mineral premix (3%). The main findings of the study were as follows: There were no significant differences among treatments in terms of final body weight, total weight gain, or average daily gain, although a numerical improvement was observed in the second treatment group (T2: 20 mg/head/day), Feed intake and feed conversion efficiency were not significantly affected by the different levels of nano zinc oxide supplementation. A significant increase (P ≤ 0.05) was observed in the mean total bacterial count and cellulolytic bacteria in favor of the second treatment group (T2) (20 mg nZnO/head/day), along with a numerical increase in the average count of lactic acid bacteria throughout the experimental period. Additionally, a significant improvement (P ≤ 0.05) in ruminal ph value was recorded after 45 days of the experiment in favor of the T2 treatment, with a numerical increase in ph also noted after 84 days for the same group.